Athletic heart: a metabolic, anatomical, and functional study - Turpeinen, A. K.; Kuikka, J. T.; Vanninen, E.; Vainio, P.; Vanninen, R.; Litmanen, H.; Koivisto, V. A.; Bergstrom, K.; Uusitupa, M. I. (Medicine & Science in Sports & Exercise, 1996)
Previous studies have suggested a reduced glucose uptake by the athlete's heart at rest. To examine whether there is a compensatory increase in the myocardial fatty acid utilization, we studied nine male endurance-trained athletes (age 26 +/- 2 yr, VO2max 60 +/- 1 ml.kg-1.min-1, mean +/- SEM) and eight sedentary subjects (age 26 +/- 1 yr, VO2max 38 +/- 2 ml.kg-1.min-1) by single photon emission tomography using 123I-heptadecanoic acid (HDA) and mathematical modeling. Magnetic resonance imaging (MRI) and echocardiography were performed for the measurements of cardiac dimensions and left ventricular (LV) mass. No significant differences were found in the myocardial HDA beta-oxidation index (5.2 +/- 2.0 vs 7.4 +/- 1.6 mumol.min-1.100 g-1, P = NS) between endurance-trained and sedentary subjects. Fractional amounts of HDA beta-oxidation, backdiffusion, and esterification were also similar. In MRI study, LV mass was greater in the trained subjects (213 +/- 9 vs 179 +/- 10 g, P < 0.01) and in particular, LV long-axis diameter measured from the mitral valve level to the apex was increased (102 +/- 2 vs 88 +/- 2 mm, P < 0.001, trained vs sedentary subjects). VO2max correlated with LV long-axis diameter (r = 0.77, P < 0.001). In contrast to our hypothesis, myocardial HDA utilization was not enhanced in endurance-trained athletes at rest. Increases in LV mass and especially in LV long-axis diameter were observed in the athletes, indicating LV longitudinal remodeling.